Studi Kinerja Hydrophore Tank Di Atas Kapal Dengan Variasi Tekanan Kerja dan Perbandingan Volume Air Dengan Udara - Susanto Susanto; Agil Putra Jaya; Bondan Krisna Setiyawan (Jurnal Maritim Polimarin, 2022)
The use of a pressure tank with a hydrophore tank that serves to temporarily store water, with the principle of providing air pressure on the upper surface of the water in the tank. Working pressure on hydrophore operation is a very important parameter for maximum operation. Problems that often occur in hydrophore tanks are usually from the supply pump, water level in the tank, air pressure, and pressure sensors. Problems caused by pumps include pump leaks, the presence of air in the water flow. As a result, the freshwater pump for supply to the hydrophore tank is often On-Off with a very fast time duration. This research was conducted to find the right setting to maintain stable operating pressure on the hydrophore tank. The research was conducted directly on board the MV. NORDTIGER with a case study of direct problems that occur in the freshwater distribution system on board. The variables at the time of data collection were the working pressure of the hydrophore tank pressure and the water level in the tank. The operating load used in data collection is the condition of ordinary load and full load. The results of the study on the performance of the hydrohore tank by varying the water-air level, working pressure range and final loading. The shortest duration of filling time is at 50%:50% volume level composition at a pressure of 5-7 bar, while the longest filling time is at 70%:30% water-air volume level at a pressure of 3-7 bar.